Analisis Peran Corporate Social Responsibility terhadap Aspek Sosial, Ekonomi, dan Lingkungan pada Industri Ritel - Abd Rohman Taufiq; Achmad Iqbal (Universitas Pendidikan Ganesha, 2021)
Corporate Social Responsibility (CSR) is a company responsibility that not only about how to generate profits, but also pay attention to society and the environment. This study aims to analyze the CSR role of retail companies in Indonesia. This research uses a qualitative approach. The results show that retail companies in Indonesia have implemented CSR in a sustainable manner. The CSR program has implications in several aspects, including social, economic, and environmental aspects. In social programs, retail company CSR is dominated by educational assistance activities, natural disasters, and blood donors. ERAA is a company that focuses on economic aspects with community development. Environmental aspects are dominated by tree planting and energy reduction. Community Development (Comnev) should be the basis for implementing CSR programs to be more sustainable.